Analysis of Zakat Management Performance and It's Implications Achievements of Sustainable Development Goals - Fatmawatie, Naning; Fauza, Nilna; Rohmah, Elma Nur (Faculty of Economics, State Islamic University of Maulana Malik Ibrahim Malang, 2020)
The National Zakat Index is a measure of performance in zakat management. With good zakat management performance, it is expected to support the implementation of sustainable development goals (SDGs). The purpose of the study was to analyze the performance of zakat management in the City of Kediri BAZNAS based on the IZN approach and analyze its implications for SDGs' achievement. This research uses a mixed-methods approach. Non-statistical quantitative methods and non-parametric qualitative methods. The results of this study in the 2019 value of IZN is not good. Macro dimension values with index are not acceptable. Besides, the database of zakat institutions is not good. Furthermore, the micro dimension, the performance of BAZNAS in Kediri City, is quite good. The influence of the performance of zakat management on the achievement of SDGs using the ANP method. Namely, the zakat program clusters occupy the priority of the Kediri program care, besides that the SDGs cluster is without poverty. The reason is the principle of zakat distribution in the City Board of Kediri prioritizing daruriyah (primary needs). Furthermore, the preferred strategy is cooperation with the government and stakeholders.